Perceptions of cervical cancer care among Ethiopian women and their providers: a qualitative study - Sahai Burrowes; Sarah Jane Holcombe; Cheru Tesema Leshargie; Alexandra Hernandez; Anthony Ho; Molly Galivan; Fatuma Youb; Eiman Mahmoud (BMC, 2022)
Plain Language Summary Cervical cancer is the second most commonly diagnosed cancer among Ethiopian women, killing an estimated 4700 women each year. This study aimed to assess patient and provider experiences in receiving and providing cervical cancer screening, diagnosis, and treatment. We interviewed 30 midlevel providers and ten women receiving care and held a focus group discussion with five women who were receiving treatment or who had recently completed treatment. Patients reported bottlenecks and delays at each stage of care. Low perception of risk, high stigma, and a lack of knowledge about cervical cancer among both providers and patients, were significant sources of delay in initiating care. Few patients had been aware of cervical cancer before they were diagnosed and of those who were aware, many assumed that they were not at risk because they were not sexually active. Misdiagnosis was another common source of delay. Once diagnosed correctly, women faced multiple-month delays after referrals, and, once in treatment, broken equipment and a shortage of hospital beds resulted in additional delays. The most frequently mentioned barriers to care were a lack of housing and travel funds while receiving treatment in the capital. Patient-provider communication of cancer diagnosis was often poor. Our findings suggest the need to intensify in-service training for providers, focusing initially on alerting them to cervical cancer symptoms. Better distribution of screening and diagnostic supplies to lower-level facilities and better maintenance of treatment equipment at tertiary facilities should also be a priority.